The Influence of Self-Regulated Learning Strategies Towards Academic Performance of College Students - John Mart Elesio (East Asian Journal of Multidisciplinary Research, 2023)
This research endeavor is conducted to determine the significant influence of self- regulated learning strategies towards academic performance of college students. This study utilized non-experimental quantitative research design employing descriptive correlational technique to find out the significant relationship of the variables. The data were analyzed coming from 290 participating first year students enrolled in a sectarian school in Davao City. Mean, pearson r and linear regression analysis were used to treat the gathered data. The findings of this study led to the following conclusions: The level of self-regulated learning strategies and academic performance were both assessed high. This means that the two variables were oftentimes observed by the college students. Moreover, there is a significant relationship between self regulated learning strategies and academic performance of college student. Further, self-regulated learning strategies significant influence the academic performance of college students.